THE HERO CHARACTERS IN A BUG’S LIFE AND CLOUDY WITH A CHANCE OF MEATBALLS MOVIES - Lita Febri Rahma Wardani Setyawan; Surya Sili; Indah Sari Lubis (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni dan Budaya, 2019)
The hero characters, like most people know, are just like Superman, Spider-Man, Wonder Woman, who gain superpower, stronger than ordinary people, and fight monsters to save the world. However, there are also the hero characters that do not gain superpower. This study concerned on finding out the differences between Flik of A Bug’s Life and Flint of Cloudy with a Chance of Meatballs movies as the ordinary hero characters by using Campbell’s hero’s journey theory. This study was a qualitative research with content analysis approach. Data of this study were words including narrations and dialogues taken from A Bug’s Life and Cloudy with a Chance of Meatballs movie scripts. This study showed that Flik was a dependent hero character, while Flint was an independent one. In Flik’s case, he was considered as the dependent hero character due to his natural trait as the ant colony to put the colony above everything else. While, Flint was considered as the independent hero character based on his reasons of doing the adventure: to fulfill his own desire of being acknowledged by his dad and to show his attractive side to the girl that he fell in love with, Sam Sparks. To conclude, regardless the fact that both Flik and Flint were included as the ordinary hero characters, this study had shown they still had their own version of hero characters.